Vpliv vadbe z zmanjsanim stevilom vdihov med plavanjem na sposobnost premagovnja maksimalnih naporov pri 200 metrov kravl - Kapus, J.; Usaj, A.; Kapus, V.; Strumbelj, B. (Kinesiologia Slovenica, 2005)
The aim of the study was to ascertain how four weeks of training with reduced breathing frequency during front crawl swimming would influence a maximal 200 metres front crawl performance. Two matched groups of five recreational-level swimmers trained five times per week. During each swimming session breathing frequency was distinguished between the control (the B2 group was taking a breath every second stroke cycle) and an experimental group (the B4 group was taking a breath every fourth stroke cycle). The swimmers performed a maximal 200 metres front crawl swim with an optional breathing pattern before and after the training. Both groups swam the maximal 200 metres front crawl after the training significantly faster than before the training. The improvement was significantly greater in the B4 group than in the B2 group. Group B4 swam a maximal 200 metres front crawl after the training with fewer breaths than before the training. The breathing pattern in the B2 group was unchanged by the training. According to its lower breathing frequency, the B4 group had a significantly higher Pco2 after the training in comparison with the Pco2 before the training. Group B4 also had a higher lactate concentration, Pco2 and a lower pH than the B2 group after the training. It may be concluded that swimmers adapted to swimming with fewer breaths due to training with reduced breathing frequency (taking a breath every fourth stroke cycle) during front crawl swimming.